A revision of fossil eagle owls (Aves: Strigiformes: Bubo) from Europe and the description of a new species, Bubo ibericus, from Cal Guardiola (NE Iberian Peninsula). (18th August 2017) - Meijer, Hanneke J. M.; Pavia, Marco; Madurell-Malapeira, Joan; Alba, David M.
Abstract: The European fossil record of eagle owls, genus Bubo Duméril1806, is thought to extend back into the Miocene, but records of Bubo before the Middle Pleistocene are scarce and mainly constituted by non-diagnostic or fragmentary specimens. Apart from a number of fossil species of Bubo of uncertain validity, i.e. Bubo? florianae Kretzoi1957, Bubo lignitum Giebel1860, and Bubo perpastus (Ballman1976 ), most fossil Bubo material is unassigned to species or assigned to the extant Bubo bubo (Linnaeus 1758) on the basis of size, especially for Early Pleistocene records. Given the ambiguity about the validity of the earliest records, here we revise the pre-Middle Pleistocene fossil record of Bubo in Europe . Our results indicate that, in Europe, Bubo is first recorded in the Late Pliocene/Early Pleistocene of Italy. By the Early Pleistocene, three taxa can be distinguished: Bubo ibericus sp. nov. from Cal Guardiola (Spain), Bubo sp. nov. indet. from Soave Cava Sud (Italy) and Bubo sp. from various sites across Europe. By the Middle Pleistocene, Eurasian environments experienced a substantial increase in severity and duration of glacial periods which might have led to the replacement of extinct species of Bubo by the recent B. bubo and Bubo scandiacus .